Chemosaturation with Percutaneous Hepatic Perfusion: Outcome and Safety in Patients with Metastasized Uveal Melanoma - Dewald, Cornelia Lieselotte Angelika; Hinrichs, Jan B.; Becker, Lena Sophie; Maschke, Sabine; Meine, Timo C.; Saborowski, Anna; Schönfeld, Leon Jonas; Vogel, Arndt; Kirstein, Martha M.; Wacker, Frank K. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Purpose Chemosaturation percutaneous hepatic perfusion (CS-PHP) allows selective intrahepatic delivery of high dose cytotoxic melphalan in patients with curatively untreatable liver tumors while limiting systemic toxicity through hemofiltration of the hepatic venous blood. Aim of this study was to investigate the response to therapy, survival and safety of the CS-PHP procedure in patients with liver-dominant metastatic uveal melanoma (UM).Materials and Methods Overall response rate (ORR) and disease control rate (DCR) were assessed according to Response Evaluation Criteria In Solid Tumors (RECIST1.1). Median overall survival (mOS), median progression-free survival (mPFS) and hepatic progression-free survival (mhPFS) were analyzed using Kaplan-Meier estimation. Adverse events were evaluated with Common Terminology Criteria for Adverse Events (CTCAE) v5.Results Overall, 30 patients were treated with 70 CS-PHP in a salvage setting from October 2014 to January 2019. In total, ORR and DCR were 42.3 % and 80.8 %, respectively. Overall, mOS was 12 (95 % confidence interval (CI) 7–15) months, and both, mPFS and mhPFS were 6 months, respectively (95 % CI 4–10; 95 % CI 4–13). Adverse events (AE) most frequently included significant but transient hematologic toxicities (87 % of grade 3/4 thrombocytopenia), less frequent AEs were hepatic injury extending to liver failure (3 %), cardiovascular events including one case of ischemic stroke (3 %).Conclusion Salvage treatment with CS-PHP is effective in selected patients with UM. The interventional procedure is safe. Serious hepatic and cardiovascular events, although rare, require careful patient selection and should be closely monitored.Key Points: Citation FormatZiel Die Chemosaturation mittels perkutaner hepatischer Perfusion mit Melphalan (CS-PHP) ist ein palliatives Therapieverfahren für Patienten mit nicht kurativ behandelbaren Lebertumoren. Die CS-PHP erlaubt eine selektive intrahepatische Anreicherung von hochdosiertem Melphalan bei minimaler systemischer Toxizität durch venöse Hämofiltration. Ziel dieser Studie war es, das Ansprechen und Überleben sowie die Sicherheit der CS-PHP-Prozedur bei Patienten mit leberdominant metastasiertem Aderhautmelanom zu evaluieren.Material und Methoden Gesamtansprechrate (overall response rate, ORR) und Krankheitskontrollrate (disease control rate, DCR) wurden anhand von Response Evaluation Criteria In Solid Tumors (RECIST1.1) ermittelt. Medianes Gesamtüberleben (mOS), medianes progressionsfreies Überleben (mPFS) und hepatisches mPFS (mhPFS) wurden mittels Kaplan-Meier-Schätzer ermittelt. Nebenwirkungen wurden entsprechend der einheitlichen Terminologie-Kriterien für Nebenwirkungen (CTCAE) v5 klassifiziert.Ergebnisse 30 Patienten wurden zwischen Oktober 2014 und Januar 2019 mit 70 Chemosaturationen behandelt. Die ORR betrug 42,3 % und die DCR 80,8 %. Das mOS betrug 12 (95 %-Konfidenzintervall (KI) 7–15) Monate, das mPFS 6 (95 %-KI 4–10) und das mhPFS ebenfalls 6 (95 %-KI 4–13) Monate. Signifikante, aber transiente hämatotoxische Nebenwirkungen waren häufig (87 % Grad-3/4-Thrombozytopenie), hepatische Toxizität bis Leberversagen (n = 1/70) sowie kardiovaskuläre Komplikationen (ischämischer Insult, n = 1/70) waren selten.Schlussfolgerung Das palliative Therapiekonzept der Chemosaturation ist bei Patienten mit hepatisch metastasiertem Aderhautmelanom effektiv. Die interventionelle Prozedur ist sicher, seltene, aber schwerwiegende kardiovaskuläre und hepatische Komplikationen erfordern eine sorgfältige Patientenselektion und intensive Aufmerksamkeit.Kernaussagen: Zitierweise
Keywords: angiography; chemotherapy; interventional procedures; percutaneous; interventional oncology